Problemi vstanovlennâ ìstini u krimìnal′nih spravah - Pavlišin, Andrìj (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2011)
The article is devoted to the issues of establishing the truth in criminal cases. Both classic and modern approaches to understanding the truth in criminal proceedings are analyzed, as well as the latest trends in knowledge and practical materials. On this basis, the author comes to the conclusion that it’s impossible to establish the objective truth in the criminal case in practice, and thus, the objective truth has to be substituted for the formal or procedural truth.
Keywords: prawda; wiedza; prawda obiektywna; prawda formalna